Traditional Chinese medicine in treating ischemic stroke by modulating mitochondria: A comprehensive overview of experimental studies - Liu, Lu; Chen, Daohong; Zhou, Ziyang; Yuan, Jing; Chen, Ying; Sun, Mingsheng; Zhou, Mengdi; Liu, Yi; Sun, Shiqi; Chen, Jiao; Zhao, Ling (Frontiers in Pharmacology, 2023)
Ischemic stroke has been a prominent focus of scientific investigation owing to its high prevalence, complex pathogenesis, and difficulties in treatment. Mitochondria play an important role in cellular energy homeostasis and are involved in neuronal death following ischemic stroke. Hence, maintaining mitochondrial function is critical for neuronal survival and neurological improvement in ischemic stroke, and mitochondria are key therapeutic targets in cerebral stroke research. With the benefits of high efficacy, low cost, and high safety, traditional Chinese medicine (TCM) has great advantages in preventing and treating ischemic stroke. Numerous studies have explored the effect of TCM in preventing and treating ischemic stroke from the perspective of regulating mitochondrial structure and function. In this review, we discuss the molecular mechanisms by which mitochondria are involved in ischemic stroke. Furthermore, we summarized the current advances in TCM in preventing and treating ischemic stroke by modulating mitochondria. We aimed to provide a new perspective and enlightenment for TCM in the prevention and treatment of ischemic stroke by modulating mitochondria.